Introduction to microkinetic modeling - Filot, I.A.W (2018)
This book started out as two separate documents. One was a set of exercises for the Advanced Thermodynamics and Catalysis course and the other was a method and theory section at that time envisioned for my PhD thesis. Only a very small part of the material in this book eventually made it into the thesis, as the whole would be much too elaborate!